Authority of the Indonesian National Army in Prevention and Eradicatiion - Syafei, Imam; Marwan (Dinasti Research, 2025)
The purpose of analyzing and finding the form of terrorism that is the authority of the Army in preventing and eradicating it. This research is a normative legal research, to determine the differences and similarities between the legal systems of one country and another. Comparison of Indonesia and Malaysia. In the procedure for handling cases of terrorism crimes in accordance with Law Number 15 of 2003, it must be carried out by state institutions that are given authority with a full sense of responsibility and seriousness. Both from the TNI, Police and State Intelligence Agency in the context of the investigation and arrest process which both support the smoothness of the investigation process that will be held later. The use of military force to combat terrorism is not taboo, both from a domestic political perspective, in the context of the international humanitarian law framework, and the provisions of the Charter and various UN resolutions. The TNI as a state defense tool, functions as a deterrent against every form of military threat and armed threat from outside and within the country against the sovereignty, territorial integrity, and safety of the nation. Such provisions are in line with what is formulated in Article 30 Paragraph (2) of the 1945 Constitution which reads,